More on Multidimensional Portfolio Analysis - Jean, William H. (Journal of Financial and Quantitative Analysis, 1973)
In response to the suggestions of the editorial and reviewing staff of this journal, some additional explanation and extensions of the model presented in an earlier paper [4] seem desirable at this time. In that paper the investor in securities was assumed to have a utility function that depended on the first n moments of the statistical distribution of returns rather than just on the mean and variance. When the borrowing-lending possibility was introduced as in the Sharpe-Lintner model, the investor's perceived risk premium could be expressed in the higher moments' dimensions as well as in terms of the variance.